Investigation Binding Patterns of Human Carboxylesterase I (hCES I) with Broad Substrates by MD Simulations - Chu, Huiying; Min, Hanyi; Zhang, Mingbo; Shen, Hujun; Li, Guohui (Current Topics in Medicinal Chemistry, 2013)
Human carboxylesterase I (hCES 1) plays an important role in the metabolism and activation of prodrugs, such as, the hydrolysis of a variety of drugs of prodrugs featuring an ester, amide or carbamate function. The bindings of the substrates of different lengths and cocaine to hCES1 at two different binding sites, catalytic site and Z-site, were studies through MD simulations. For each case, the correlation analysis has been performed to explore the binding patterns of a broad range of substrates binding to the hCES1.
Keywords: molecular simulations